Platinum Coating on an Ultrathin InN Epilayer as a Dual Gas Sensor for Selective Sensing of Ammonia and Acetone by Temperature Modulation for Liver Malfunction and Diabetes Applications. (1st January 2018) - Rai, Sujeet Kumar; Kao, K.W.; Agarwal, Ashish; Gwo, S.J.; Kumar, Amarendra; Yeh, J. Andrew
Abstract : A platinum coating on an ultrathin InN resistive gas sensor was fabricated for the selective sensing of ammonia and acetone gas for liver malfunction and diabetes applications by using a temperature modulation technique. We use a cyclic temperature profile in the InN gas sensor heater, where the temperature varies from 200°C to 0°C and from 0°C to 200°C in increments of 50°C. Therefore, a different current variation response is measured on an InN epilayer for 5 ppm ammonia and 5 ppm acetone gas, respectively, because ammonia and acetone gas behave differently in the cyclic temperature profile. When ammonia and acetone gas are exposed in background air, the variation in the response of the current in different temperature regions is given as 2.5% for acetone gas and 7.85% for ammonia gas between 100°C to 150°C, and 12% for acetone gas and 8.85% for ammonia gas between 150°C to 200°C. Therefore, the temperature region 100°C to 150°C is suitable for selectively sensing ammonia gas for determining liver malfunction. The temperature range between 150°C to 200°C is suitable for selectively sensing acetone gas for the diabetes monitoring applications.